Illuminating the importance of learning interaction to Open Distance Learning (ODL) success: A qualitative perspectives of adult learners in Perlis, Malaysia - Dzakiria, Hisham (2012)
Open Distance Learning (ODL) provides learners with the greatest possible control over time, place and pace of education.The educational delivery of ODL has improved greatly over the years with growing number of students continuously enrolling into various ODL programs globally. ODL however does come with issues and problems. Loss of student motivation due to the lack of learning interaction with peers, tutors and computer skills are some possible to ODL.Interaction is a fundamental instructional component to ODL.It is the most challenging element to build into an ODL system and delivery that fit-all-learner needs and requirements.The level of interactivity within the interaction triads from student-to-student, student-to-tutor, and student-to-interface (technology) has a major impact on the quality of ODL programs and its educational experience. Research studies on interactivity show that learners have a real need to make connections with their peers, tutors and the technology use in their pursue for learning, and this research reports similar findings.This article is based on a qualitative research investigating issues of learning interaction in ODL of eight adult learners in the state of Perlis, Malaysia. The study findings supported the widely held belief that a high level of interaction is desirable in ODL environment (Anderson, 2003; Tinto, 2002; Dzakiria, 2008; Dzakiria & Idrus, 2003; Rumble, 2000; Walker, 2002) and positively affects the learning experiences. In order to improve ODL experience, this research suggests that all-important stakeholders in ODL must improve the provision of interaction and interactivity.